Blood Donors Recruitment and Incentives in Bangladesh (TAJ: Journal of Teachers Association, 2009)
The potential effectiveness of various donation incentive programs may vary by demographics and first time or repeat status. Attitudes towards future incentives were obtained from 2,897 whole blood donors among 5,357 allogenic donors who return a questionnaire (54.08% response rate). Majority were first time donors 67.59% (1,958) with 32.41% (939) repeated donor. Majority of the respondents were male 68.52% (1,985), female 31.48% (912). Responses to incentives were compared between first time and repeat whole blood donors. Incentives most likely to encourage donation return among all 2,897 whole blood respondents were blood screening test (B.S.T), against transfusion transmitted infection (T.T.I) 71.65%, blood credits- 61.55%, cash to charity- 43.35% and gift- 27.6%. The incentives that would be least likely to encourage return were a token or award of appreciation- 15.85%. Few donors would be discouraged to return if offered B.S.T against T.T.I (0.25%), other miscellaneous incentives (1.31%), a gift (2.15%), a token of appreciation (1.95%). Compensatory incentives could potentially have a more negative impact because 7 to 9 percent of donors reported they would be discouraged for donating if they received cash or lottery or raffle ticket. Young (18-25 years old) donors were encouraged by B.S.T against T.T.I (58.4%) and older (51 years old) donors (58.4%); more than 2 hours off work (46.2% and 13.7%); community service and / or education credits ( 44.2% and 10.7%); or compensatory incentives (56.9% and 15.8% for cash to charity 57.8% and 26.7%); gifts (39.6% and 11.4%) or a token of appreciation (27.4% and 10.0%) respectively. Blood screening and blood credits would be well received at all donation sites. Gift, compensatory incentives and token of appreciation appeal more to younger donors. These data may allow blood centers to optimize recruitment by tailoring limited incentive recourses more effectively. doi: 10.3329/taj.v20i2.3074 TAJ 2007; 20(2): 129-135